Withdrawal of antibiotic growth promoters in China and its impact on the foodborne pathogen Campylobacter coli of swine origin - Wen, Renqiao; Li, Chao; Zhao, Mengyu; Wang, Hongning; Tang, Yizhi (Frontiers in Microbiology, 2022)
Antibiotic growth promoters (AGPs) have been used as feed additives to improve feed efficiency in food animals for more than six decades. However, the wide use of AGPs has led to the emergence of antibiotic-resistant pathogens of animal origin, posing a significant threat to food safety and public health. China prohibited the addition of AGPs to animal feed from July 2020. The impacts caused by the withdrawal of AGPs on the prevalence and antibiotic resistance of foodborne pathogens have not been illustrated. Here, a total of 471 strains of Campylobacter were isolated from pigs from three pig farms and two slaughterhouses in Sichuan Province for four consecutive years (2018-2021), including two years before and two years after the ban on AGPs in China. The isolation rate of Campylobacter had a slight increase after prohibiting the addition of AGPs to the feed. Contrary to what we expected, the antibiotic susceptibility test and WGS data showed that the antibiotic resistance to gentamicin and florfenicol and the abundance of virulence genes increased significantly after the ban of AGPs. Comparison of the isolates of swine origin with isolates of human origin indicated the potential of antibiotic-resistant Campylobacter transmission from pigs to humans. These data suggested that phasing out AGPs may lead to increased use of therapeutic antimicrobials, promoting the prevalence and transmission of both antibiotic resistance and virulence genes.